Relationship between nutrition pattern, personal hygiene, and postpartum mobilization with the risk of purulent lochia discharge - Fitria Aisyah; Mufida Annisa Rahmawati; Woro Tri Utami (CV. LINK Education Publication, 2025)
Introduction: Lochea purulenta is a fluid that comes out of the uterus that passes through the vaginal opening with different characteristics and after delivery. The cause of the occurrence of lochea purulenta due to poor Hygnie Poor nutrition and lack of mobilization. Objectives: nutrition pattern, personal hygiene, and postpartum mobilization with the risk of purulent lochea discharge Methods: This type of research is quantitative, and the method in this study uses an analytical survey with the approach taken is cross-sectional. The population in this study were postpartum mothers on day 4–7, which amounted to 30 people. The sample in this study were all 4–7 day postpartum mothers totaling 30 people. The sampling technique in this study is Total Sampling. Variable is nutrition relationship, personal hygiene, mobilization, and variable Y is lochia purulenta. Data collection methods used were questionnaires, observation, interviews, and documentation. Data were analyzed using multiple linear regression calculations. Results: The nutritional pattern and personal hygiene have a significant relationship with the risk of lochia purulenta, with t-values of 2.373 > t table 2.056 and 2.307 > t table 2.056 (p-value < 0.05), respectively. On the other hand, mobilization does (not have a significant relationship with lochia purulenta because the t-value is 1.194 < t table 2.056 (p-value > 0.05). Simultaneously, there is a significant relationship between X1, X2, and X3 and Y, with an F value of 5.230 > F table 2.975 (p-value < 0.05). The most dominant variable related to the risk of lochia purulenta is nutritional pattern. Conclusion: There is a significant relationship between the nutrition pattern, personal hygiene, and postpartum mobilization with the risk of purulent lochea discharge. Postpartum health programs should place greater emphasis on monitoring nutrition and personal hygiene, while considering the importance of mobilization in the recovery process.